Advances in Flexible Optoelectronics Based on Chemical Vapor Deposition‐Grown Graphene (Adv. Funct. Mater. 42/2022). (18th October 2022) - Du, Jinhong; Tong, Bo; Yuan, Shuangdeng; Dai, Nian; Liu, Rui; Zhang, Dingdong; Cheng, Hui‐Ming; Ren, Wencai
Abstract : Flexible Optoelectronics In article number 2203115, Wencai Ren and co‐workers review the recent advances and significant developments of chemi cal vapor deposition‐grown graphene toward flexi ble optoelectronics. Various prototype devices including photodetectors, organic solar cells, and light emitting diodes are demonstrated. These devices are available to large‐area fabrication and have good flexibility, showing great potential to integration of multifunctional wearable systems based on chemical vapor deposition‐grown graphene.